ALCOHOL ATTENDANCE WITHIN THE EMERGENCY DEPARTMENT. Issue 10 (7th September 2013) - Kelly, G; Crick, J; Hall, T
Abstract : Objectives & Background: How much does alcohol contribute to the demands on the Emergency Department (ED)? York is a popular tourist destination, particularly amongst hen and stag parties. But a quarter of the resident population have previously been identified as higher risk drinkers. So therefore, how much does alcohol contribute to the pressures on York ED? Additionally, clinical coding of alcohol within the ED is anecdotally unreliable. How true is this? We therefore undertook an alcohol needs assessment within York ED looking at general demographics, reasons for attendance and evidence of alcohol linked to the attendance. We also looked at the discrepancy between how much the ED was paid for these patients by commissioners and the actual cost to the acute trust. Methods: We randomly selected 1 week per quarter in 2011 and hand searched every ED record for evidence of alcohol-related attendance. We also included patients for whom it was felt alcohol was highly likely although not directly mentioned. We undertook a concordance assessment around the alcohol question and achieved 94%. Results: The 4 randomly selected weeks amounted to a 5, 704 patient sample, 7.2% of the total number of attendances in 2011. 9.8% of attendances were alcohol-related (553 patients) Between 21:00 and 09:00, this rose to 19.7% Alcohol was involved in 45% of mental health attendances The alcohol group was heavily over-represented in the patients removed by police (100%), refusing treatment (55%) and leaving prior to their treatment (41%) 10.3% of alcohol-related attendees remained in the ED for >4hours compared with 5.9% of non-alcohol-related attendees 62.8% of alcohol-related attendees were living within the City of York 18% of all ambulance journeys were due to alcohol Although 553 patients had evidence of alcohol in their attendance, it was only coded as such in 46 computer records If these figures are extrapolated to cover the annual patient population, the discrepancy between what the commissioners pay and the true cost of these patients is £552, 431 Conclusion: Alcohol poses a disproportionate burden on York Emergency Department and Yorkshire Ambulance Service. With pressures on staffing, the 4 hour standard and ambulance turnaround times at an all-time high, how different would the ED be if the alcohol burden were reduced? This needs assessment fuels the argument for an 'invest to save' attitude to reduce alcohol-related attendance.